The Effect Of Cocoa Cream (Theobroma Cacao L) Administration On Breast Engorgement In Primigravida Postpartum Mothers - NATHASIA HARYONO; Sri Putriani Sinaga; Fiyola Ladyvia; Ismah Khaerunisa (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Breast engorgement is a common problem among postpartum mothers, especially primigravida, which can cause pain, swelling, and hinder the breastfeeding process. Conventional management such as warm compresses often provides only temporary relief, thus alternative therapies that are more effective and natural are needed. Cocoa (Theobroma cacao L.) contains flavonoids, polyphenols, and cocoa butter with anti-inflammatory, antioxidant, and emollient properties. This study aimed to determine the effect of cocoa cream on reducing breast engorgement in primigravida postpartum mothers. This research employed a quasi-experimental design with a pretest-posttest control group approach. A total of 36 primigravida postpartum mothers were recruited and divided into two groups: the intervention group (cocoa cream) and the control group (warm compresses). Measurements were conducted on days 1, 3, 5, and 7 using breast circumference measurement and the Visual Analog Scale (VAS) for pain. Data were analyzed using Paired t-test and Independent t-test with a significance level of p<0.05. Independent t-test results showed no significant differences at pretest (p=0.674) and day 3 (p=0.068). However, significant differences were observed from day 5 (p=0.003) and became more pronounced on day 7 (p=0.000), with the intervention group demonstrating greater reduction in pain and swelling compared to the control group. Cocoa cream was more effective than warm compresses in reducing breast engorgement among primigravida postpartum mothers, particularly after the fifth day postpartum. Cocoa cream may be recommended as a safe, natural, and non-invasive complementary therapy to support successful breastfeeding.